Organizational Management of SMP IT Mutiara in Improving Teacher Professionalism through Academic Supervision - Hadi, Riswan (Continuous Education: Journal of Science and Research, 2025)
This study aims to analyze the organizational management pattern at Mutiara IT Junior High School and the implementation of academic supervision as a strategy to improve teacher professionalism and its impact on learning quality. The approach used is qualitative with data collection techniques through interviews, observation, and documentation. The results show that Mutiara IT Junior High School implements collaborative, participatory, and structured-based organizational management, with transformational principal leadership. The open organizational structure enables effective coordination in the implementation of academic supervision. Academic supervision is conducted systematically and sustainably with an approach of mentoring, reflection and adjustment based on teachers' needs and the learning context. The implementation of this supervision increases teachers' awareness of the importance of reflective learning and continuous professional development. The positive impact is seen in the improvement of pedagogical competence, commitment to duty, and active participation of teachers in self-development. These findings confirm the importance of effective organizational management and academic supervision in creating a productive and innovative educational ecosystem. Thus, Mutiara IT Junior High School serves as a best practice model for managing school organizations to support teacher professionalism and education quality.